Understanding Novice Teachers' Thinking About Student Assessment (Alberta Journal of Educational Research, 1999)
This study captures novice teachers' efforts to mark, grade, and report on the language arts achievement of a fictional grade 8 student named Chris. Although it was not mandated, commenting on Chris's loork was seen by them as a professional responsibility. Although comments were numerous, relatively few were specific enough to provide guidance in how to improve writing. Grading was influenced by the prescribed grading policy, but also the perceived appropriateness of the assessment instruments and by a holistic impression participants developed about their particular Chris. Student assessment emerges as a complex process influenced by the teacher, the learner, the learning environment, and the principles of measurement. Findings from this study suggest that professional knowledge about assessment developed in isolation from the complex contexts of classrooms will probably remain unconnected and underused.